Toward an integrated framework of corporate venturing for organizational ambidexterity as a dynamic capability - Lysander Weiss; Dominik K. Kanbach (Management Review Quarterly, 2021)
In times of changing business environments, firms must constantly renew their competitive advantage by establishing dynamic capabilities. While often attempting to employ this in corporate venturing activities, they face the challenge of simultaneously exploring new and exploiting existing business opportunities. Examining possible approaches to mastering this feat of 'organizational ambidexterity' reveals an extensive but scattered picture. To better integrate this effort by assessing how corporate venturing is linked with organizational ambidexterity in the literature and identifying possible organizational setups, this systematic literature review builds on a sample of 172 studies. Based on different dimensions of dynamic capabilities, the analysis indicates that corporate venturing may take a solely explorative or an exploitative role, or balance both, to directly enable organizational ambidexterity, following a 'trade-off', respectively 'paradox', school of thought. As a result, this paper identifies four different setups of corporate venturing in an integrated framework, based on the ability and approach to enabling organizational ambidexterity. Here, the synthesis in the proposed framework of the studies examined allows differentiating between not directly ambidextrous separated or integrated corporate venturing and directly ambidextrous contextual or interlinked corporate venturing. As a novel contribution to the fields of strategic management, organizational change and corporate entrepreneurship, this integrated perspective suggests an often overlooked, potentially more strategic role for corporate venturing in the strategic renewal of a firm's competitive advantage, thus building the basis for further empirical research on strategic corporate venturing approaches for organizational ambidexterity and their application in practice.
Keywords: M1; M10; M13; 650; Organizational ambidexterity; Corporate venturing; Corporate innovation; Dynamic capabilities; Strategic management; Corporate entrepreneurship